2015
DOI: 10.1038/ncomms9750
|View full text |Cite
|
Sign up to set email alerts
|

Opposite correlations between cation disordering and amorphization resistance in spinels versus pyrochlores

Abstract: Understanding and predicting radiation damage evolution in complex materials is crucial for developing next-generation nuclear energy sources. Here, using a combination of ion beam irradiation, transmission electron microscopy and X-ray diffraction, we show that, contrary to the behaviour observed in pyrochlores, the amorphization resistance of spinel compounds correlates directly with the energy to disorder the structure. Using a combination of atomistic simulation techniques, we ascribe this behaviour to str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 68 publications
2
48
1
Order By: Relevance
“…Indeed, we observed trapping when intrinsic (non-structural) oxygen defects were simulated 17 . Our results are also contrary to observations in spinel 37 and perovskites 38, 39 , where the oxygen vacancy diffusivity is hindered by cation disorder. While in perovskites, cation ordering was shown to open particular channels for fast diffusion; 39, 40 , the effect of ordering in spinel is less clear.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Indeed, we observed trapping when intrinsic (non-structural) oxygen defects were simulated 17 . Our results are also contrary to observations in spinel 37 and perovskites 38, 39 , where the oxygen vacancy diffusivity is hindered by cation disorder. While in perovskites, cation ordering was shown to open particular channels for fast diffusion; 39, 40 , the effect of ordering in spinel is less clear.…”
Section: Discussioncontrasting
confidence: 99%
“…One reason for the different behavior could be that the antisite network was fundamentally different in the simulations from ref. 37 , either because of the way it was generated (using Monte Carlo in that study versus random generation here) or the crystal structure and stoichiometry of the two materials leads to different relationships between antisite environments. (Indeed, short range order has been observed in irradiated pyrochlores 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…0.5 MgO−Al 2 O 3 exhibited the highest degree of inversion, concentration of medium‐strength basic sites, and CO 2 uptake. We therefore propose that a high degree of inversion with highly basic Mg–O ion pairs of unsaturated oxygen sites is key for highly efficient MgO−Al 2 O 3 sorbents …”
Section: Resultsmentioning
confidence: 99%
“…The normal/inverse phase transition at 25 °C seems not very realistic, because it is generally accepted that with increasing temperature T the site occupancy, and thus the inversion degree x , becomes increasingly random , with no sharp transition temperature. In a more recent paper Sickafus together with other authors reported MgGa 2 O 4 as random spinel, but gave x = 0.67–0.9, which tends actually already to “largely inverse”. The somewhat controversial data on site occupancy which are found also for several other spinels indicate, that occupancy might depend on the thermal history of the sample.…”
Section: Introductionmentioning
confidence: 89%